310 PROTEINURIA IN SURVIVORS OF HANTAVIRUS PULMONARY SYNDROME. (1st January 2005) - Pergam, S.; Schmidt, D.; Glass, G.; Harford, A.; Goade, D.
Abstract : Hantavirus Pulmonary Syndrome (HPS) caused by the bumyaviridae Sin Nombre virus was first recognized in the southwestern US in the early 1990's. It has been clinically defined by cardiopulmonary collapse and is associated with high mortality. There is a relative absence of primary renal involvement when compared to Hantavirus Hemorrhagic Fever with Renal Syndrome (HFRS) seen in parts of Europe and Asia. Examination of autopsy specimens in patients with HPS did not find evidence of renal involvement. The long term side effects of HPS have not been studied extensively. A cohort of 29 HPS survivors were studied through intermittent follow-up. During visits we assessed for renal involvement with serum chemistries and 24hr-urine collections for protein and creatinine. We report that while primary renal disease is not a typical feature of acute HPS, a significant percentage of our cohort have evidence of proteinuria during long term follow-up. Our cohort of HPS survivors represents a relatively diverse group, representing different ethnicities, ages, and severity of acute illness. None of the patients appear to have significant reductions in creatinine clearance. Fifteen of 29 patients had proteinuria of at least 150mg of total protein per 24hr-urine collection. A subset of 7 survivors had at least 300mg. Many patients who developed proteinuria did not have abnormal 24hr-urine collections at first visit. There was also a trend toward increased rates of proteinuria with greater follow-up. There was a trend toward higher BMI in patients with proteinuria. In conclusion, proteinuria appears to be common in HPS survivors in the post-convalescent period. As proteinuria can be an early marker for progressive renal disease, these preliminary data represent a phenomenon that warrants further study.